The Event Communication Vector of Efficiency of Moroccan Large Companies - Najwa El Omari; Toufik Majdi (DeReMa (Development Research of Management): Jurnal Manajemen, 2016)
The event communication has for objective to give another dimension to the company or to the brand, by bringing it out of its daily life and by developing relations with its target public, around their centers of interests. It may be by sharing the same passions, by making live feelings to a group, by federating and by creating links; because today we need a more emotional and more real component.Since a few years, the event communication seems to be "revisited" by companies and appears to stand out as an alternative to media or other more traditional tools. For the upholders of the relationship marketing, this communication delivers “a social message which affects the spectator or the auditor in its inhalation to be a part of a social, sports or artistic community” (Perlstein and Picket, 1985).Therefore, we are going to expose our researches and would try to answer the following problem: "what is the impact of the event communication on the Moroccan large company, independently of any different parasite variable? ".The objective of our research is to try to make notions understand around the event communication, and especially the evaluation of its added value on the efficiency of the Moroccan large company. To try to answer these questions derived of our problem, our research will concentrate on: a first theoretical part around a set of concepts, a second part will be the object of an empirical study.